Realm of Pathological Lesions of Breast in A Tertiary Care Teaching Hospital in A Dominantly Tribal Region - KirtiPardeshi; Hoogar M.B.; Satish Bhasale; Saniya Dsouza (International Journal of Pharma and Bio Sciences, 2023)
The breast, an important organ of lactation in mammals, is one of the most common organs affected by various physiological and pathological processes. The pathological processes that affect the breast can be non-neoplastic and neoplastic lesions. The non-neoplastic lesions include aberrant development of breast infectious and inflammatory lesions. Neoplastic lesions of the breast comprise benign and malignant tumours of the breast. The present retrospective study aims to study the spectrum of lesions in pathological breast lesions. We have studied various non-neoplastic and neoplastic lesion of the breast and their clinic pathological correlation wherever possible and so also to know the incidence of various malignant lesions of the breast in a tertiary care teaching hospital. The study is conducted in the Department of Pathology, Vedantaa Institute of Medical Sciences, Palghar, Maharashtra, a predominantly tribal region, from January 2022 to April 2023. All excision and incision biopsy specimens and mastectomy specimens are included in the study. After the specimens were processed by standard tissue processing procedures of formal fixation and paraffin embedding protocol, standard paraffin sections were cut and stained with routine histopathological stain. In the results, 86 specimens from breast lesions were received, of which 91.8 % are neoplastic and 8.1 % are non-neoplastic lesions. Among neoplastic lesions, 69.7 % constituted benign lesions, commonly observed in the age group of 31-40 years, and 6.9 % are malignant lesions commonly noted in the age group of 61-70. In conclusion, it is observed that Fibroadenoma is the most common benign tumour, and Infiltrating duct carcinoma (NOS) is the most common tumour among the malignant breast. Among the special types of invasive breast carcinomas, metaplastic carcinoma of the breast with an increased incidence is an unforeseen finding of the present study.